The Status of the Education Sector in Sudan - World Bank (World Bank, 2012)
This publication is the first comprehensive overview of the education sector in Sudan. The challenge that remains is to design policy responses to the issues identified within the forthcoming education sector strategic plan. More important, these policies-already being discussed with the Ministry of General Education (MoGE) must be effectively implemented so that Sudan can make faster progress toward achieving the Education for All (EFA) targets and Millennium Development Goal's (MDGs). It is my hope that this report will serve as the basis for an evidence-based and equity oriented approach to education planning and investment. This approach will have positive repercussions for overall economic growth, poverty alleviation, and human development in 21st-century Sudan. This report was prepared in collaboration with a national team from the MoGE and partners active in the education sector in Sudan. Over a period of 18 months, this collaboration facilitated considerable capacity building in data collection and analysis, as well as regular dissemination of the analysis to a wider audience.